Maturasi Gonad Bawal Bintang (Trachinotus blochii) dengan Induksi Hormon Human Chorionic Gonadotropin (hCG) dan Pregnant Mare Serum Gonadotropin (PMSG) - Wiwin Kusuma Atmaja Putra; Rian Hadrianto; Tengku Said Razai (Jurnal Perikanan Universitas Gadjah Mada, 2017)
Human Chorionic Gonadotropin (hCG) and Pregnant Mare Serum Gonadotropin (PMSG) hormone is a product that contains the hormone Folicle Stimulating Hormone (FSH) and Litiunizing hormone (LH) that play a role in regulating the development gonad process of fish. This research determine to effect hCG and PMSG hormone induction and find out the best treatment in the induction on gonad maturation of Silver pompano fish. This research used three treatments: control (NaCl), hormone hCG 20 IU.kg-1 and PMSG 20 IU.kg-1 fish body weight. Containers used in the maintenance of fish in the form of Floating Net Cage (KJA) with size 3x3x3 m. The best research result is 20 IU PMSG treatment with GSI value equal to 0.6%, HSI equal to 1.25%, maturity level of gonad reaches TKG III and histologically progress reach secondary oocyte and primary oocyte. The conclusion of this research is hCG and PMSG hormone induction effect on gonad maturation Silver pompano fish for 4 weeks compared to control treatment. The best hormone treatment is PMSG hormone treatment with a dose of 20 IU. Kg-1 fish body weight.